ASISTENSI PENGGUNAAN PENDEKATAN KONSTRUKTIVISME DENGAN MEDIA PENDAMPING EDMODO UNTUK GURU SMA/MA MGMP EKONOMI SE-KOTA PADANG - Sri Wahyuni; Jimi Ronald; Vivina Eprillison; Mona Amelia; Dio Fernando (STKIP PGRI Sumatera Barat, 2019)
Currently there are a variety of new innovations in the world of education, especially in the learning process. One such innovation is constructivism. The choice of approach is more so that learning makes students enthusiastic about existing problems so they want to try to solve the problem. Classroom learning that uses constructivism, will make students empowered by the knowledge within them. They share strategies and solutions, debate one another, think critically about the best way to solve each problem. In this case Edmodo provides an environment where teaching and learning can produce student excitement that will make students more independent without forgetting the standards for measuring student success. It is undeniable that students will like learning through this platform, and when students feel comfortable, their desire to be able to understand new material, and the spirit of overcoming difficulties will increase in the learning process. Edmodo is one of the ways to build student enthusiasm for learning. Edmodo can help teachers build a virtual classroom based on the division of real classes in schools, where in the class there are assignments, quizzes, and grading at the end of each learning.